Impact of Transformational Leadership on Professional Learning Community: Mediating Role of Emotional Intelligence - Ibrahim, Nor Azlin; Hamzah , Mohd Izham Mohd; Abdul Wahab, Jamalul Lail (International Journal of Psychosocial Rehabilitation, 2020)
The Professional Learning Community (PLC) that was introduced by the Teacher Education Division or known as Bahagian Pendidikan Guru (BPG) serve the purpose to realize KPM’s aspiration which is to deliver quality teachers in terms of teaching and learning. Consequently, the principal, who functions as a driving force in the school, must employ an energetic leadership style to accomplish this goal. Hence, the objective of this research is to recognize the relationship of principal’s transformational leadership practice to the practice of the professional learning community of teachers in high performance school or known as Sekolah Berprestasi Tinggi (SBT). Another aim is to identify the role of the principal’s emotional intelligence as a mediator in the relationship. Three hundred sixty-four teachers were selected as samples from 34 secondary schools in the SBT category in Malaysia. The survey method was conducted utilizing the questionnaire instrument. Data were analyzed applying Partial Least Squares-Structural Equation Modeling (PLS-SEM) version 3.0 software. The findings show that there is a relationship between leader’s transformational leadership and the teacher’s professional learning community. Besides, the study unveiled that emotional intelligence works as mediating role in the relationship.